2011
DOI: 10.1002/adv.20239
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fiber fabric reinforced PPS laminates: Influence of temperature on mechanical properties and behavior

Abstract: This paper is aimed at investigating the influence of temperature on mechanical properties and behavior of carbon fiber fabric reinforced polyphenylenesulfide (PPS) laminates subjected to different loadings: tensile, open hole tensile, in-plane shear, compressive, flexural, interlaminar shear, single-bolt double lap joint, and single-bolt single lap joint tests. The resulting experimental database is of the utmost importance for generating design allowables for structures integrating such thermoplastic-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…However, this failure mode was relatively rarely observed. Most of samples showed large plastic deformation with or without a small drop of stress after the elastic region (see Figure 13B) which can reveal the presence of crack propagation (van Rijswijk et al, 2009;Vieille et al, 2011;See et al, 2015;Obande et al, 2019). According to these results the failure mode cannot be directly related with the pressure level of the consolidation.…”
Section: Influence Of Compaction Pressurementioning
confidence: 87%
“…However, this failure mode was relatively rarely observed. Most of samples showed large plastic deformation with or without a small drop of stress after the elastic region (see Figure 13B) which can reveal the presence of crack propagation (van Rijswijk et al, 2009;Vieille et al, 2011;See et al, 2015;Obande et al, 2019). According to these results the failure mode cannot be directly related with the pressure level of the consolidation.…”
Section: Influence Of Compaction Pressurementioning
confidence: 87%
“…The DIC approach reveals the strain measurement on the specimens to restrict only in the region around the machined holes during the tensile test. 14 The failure characteristics of CFRP were also examined during the tensile test using a thin PZT piezoelectric ceramic plate, φ 9.0 × 0.12( t ) mm, which attached on the specimen directly. Concept of this approach is related to the acoustic emission method for detection of the localized failure.…”
Section: Methodsmentioning
confidence: 99%
“…They found that those nanoparticles showed great potential to improve the mechanical and tribological properties of conventional thermoplastic/CF composites for structural applications. Liu et al [26] explored the interfacial micromechanical performance of carbon fiber T (CF) reinforced polyphenylene sulfide (PPS) composites by micro-bond test and concluded the interfacial shear strength increased with increasing fiber embedded length below 0.02 mm/s and above 0.04 mm/ s. Vieille et al [27] investigated the influence of temperature on mechanical properties and behaviors of carbon fiber fabric reinforced polyphenylene sulfide (PPS) laminates subjected to different loadings and they exhibited that a temperature up to the glass transition temperature (T g ) softens the matrix behavior and reduces mechanical properties (in-plane shear, compressive, flexural and interlaminar shear).…”
Section: Introductionmentioning
confidence: 99%